A carbon carrier and a method for preparing the same

By using the same carbon source to prepare carbon support, ensuring the consistency of internal and external graphitization, the problem of difficulty in taking into account both the stability of the existing carbon support structure and specific surface area is solved, and efficient catalyst loading and utilization rate is achieved.

CN119733494APending Publication Date: 2025-04-01SUZHOU HYDROGINE POWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411940910.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing carbon support is difficult to take into account both the structural stability and specific surface area, and the degree of graphitization of the core and shell materials in the core-shell structure is inconsistent, resulting in difficulty in regulating the pore structure.

Method used

The same carbon source is used as the core and shell components of the precursor, and the degree of graphitization in and out is consistent through heat treatment, forming a structure in which the shell is mesoporous carbon and the core is solid carbon.

Benefits of technology

The consistency of the degree of graphitization inside and outside the carbon support is achieved, the structural stability and specific surface area of ​​the support are improved, and the utilization rate of catalyst load is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733494A_ABST
    Figure CN119733494A_ABST
Patent Text Reader

Abstract

A carbon carrier and a preparation method thereof, belonging to the field of catalyst technology; the method comprises: obtaining a precursor, the precursor comprising a core and a shell, the components of the core comprising a first carbon source, the components of the shell comprising a second carbon source and a template pore-forming agent, the first carbon source and the second carbon source being the same; heat treatment to remove the template pore-forming agent in the shell of the precursor and carbonization treatment to obtain a carbon carrier; by using the same carbon source as the components of the core and shell of the precursor, in the subsequent heat treatment process, the decomposition degree and shrinkage degree of the core and the shell are consistent, and the graphitization degree of the core and the shell are consistent. In addition, the core size and shell thickness of the carbon carrier prepared by the method are controllable, which is conducive to adjusting the carrier size and mesopore depth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of catalyst technology, and in particular, to a carbon carrier and a preparation method thereof. Background Art

[0002] At present, carbon carriers are mainly divided into solid carbon and porous carbon. Solid carbon has strong structural stability but small specific surface area, which is not conducive to increasing the catalyst loading. Porous carbon has a high specific surface area but a loose structure and poor stability. When used as a carrier, it is easy to make the catalyst particle loading position too deep, reducing the utilization rate. In the current core-shell structured carbon materials, the core and shell are made of materials of different textures. The core generally uses existing carbon black materials, phenolic resin balls, metal organic frameworks, etc., and the shell is generally made of biomass carbon sources, polymers and other materials. The core and shell of different texture materials have large differences in internal and external component structures after high-temperature treatment, resulting in structural characteristics such as inconsistent internal and external graphitization degrees and difficult to control pore structures. Summary of the invention

[0003] The present application provides a carbon carrier and a preparation method thereof, which can form a structure in which the internal and external components and the degree of graphitization are consistent, and the shell layer is a mesoporous carbon core and the solid carbon.

[0004] In a first aspect, an embodiment of the present application provides a method for preparing a carbon carrier, the method comprising:

[0005] Obtaining a precursor, the precursor comprising a core and a shell, the core comprising a first carbon source, the shell comprising a second carbon source and a template pore-forming agent, the first carbon source and the second carbon source being the same;

[0006] The precursor is heat-treated to remove the template pore-forming agent in the shell layer of the precursor, and carbonized to obtain a carbon carrier.

[0007] In the above implementation process, by using the same carbon source as the core and shell components of the precursor, the decomposition degree and shrinkage degree of the core and shell are consistent during the subsequent heat treatment process, such as carbonization treatment, etc., which can ensure the consistency of the graphitization degree inside and outside the heat-treated carbon material. In addition, the core size and shell thickness of the carbon carrier prepared by this method are controllable, which is conducive to adjusting the size of the carbon carrier and the pore depth.

[0008] As an optional embodiment, the first carbon source and the second carbon source include phenolic resin.

[0009] As an optional embodiment, the template pore former includes a polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer (F127) and / or a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123).

[0010] The weight average molecular weight of the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer is about 12,600, and the weight average molecular weight of the polyethylene oxide-polyoxypropylene oxide-polyoxyethylene oxide triblock copolymer is about 5,800.

[0011] As an optional embodiment, the obtaining of the precursor comprises:

[0012] Mixing the core raw material with a solvent to obtain a first mixed material;

[0013] subjecting the first mixed material to a polymerization reaction to obtain a solution containing a core;

[0014] Mixing the core-containing solution, shell layer raw materials and template pore-forming agent to obtain a second mixed material;

[0015] subjecting the second mixed material to polymerization reaction to obtain a precursor;

[0016] The core raw material is the same as the shell raw material, and the core raw material includes phenol and its derivatives and aldehyde substances.

[0017] In the above implementation process, a one-pot method is adopted to first prepare the core, and then continue to add the raw materials of the shell layer, and continue to grow on the basis of the core to obtain a precursor, thereby maintaining a high dispersion state of the core and achieving a more uniform shell coating.

[0018] As an optional embodiment, in the first mixed material, the molar concentration of the phenol and its derivatives is 0.01 mol / mL to 0.1 mol / mL;

[0019] In the first mixed material, the molar concentration of the aldehyde substance is 0.01 mol / mL to 0.1 mol / mL;

[0020] The first mixture also includes an alkaline catalyst, and the alkaline catalyst includes at least one of ammonia water, potassium hydroxide and sodium hydroxide;

[0021] The pH value of the first mixed material is 9-13.

[0022] In the above implementation process, by controlling the concentration of phenol and its derivatives, the concentration of aldehyde substances, and the pH value of the reaction system during the polymerization of the core, it is beneficial to form a better phenolic resin as a core carbon source, which is beneficial to the formation of a high-quality carbon carrier core.

[0023] As an optional embodiment, in the second mixed material, the molar concentration of the phenol and its derivatives is 0.01 mol / mL to 0.1 mol / mL;

[0024] In the second mixed material, the molar concentration of the aldehyde substance is 0.01 mol / mL to 0.1 mol / mL; and / or

[0025] In the second mixed material, the molar concentration of the template pore-forming agent is 0.01 mol / mL to 0.1 mol / mL.

[0026] In the above implementation process, by controlling the concentration of phenol and its derivatives, the concentration of aldehyde substances, and the concentration of template pore-forming agent during the polymerization of the shell layer, it is beneficial to form a better phenolic resin as a shell carbon source and better pores, which is beneficial to the formation of a high-quality carbon carrier shell layer.

[0027] As an optional embodiment, the heating rate of the heat treatment is 0.5°C / min to 3°C / min; and / or

[0028] The heat treatment temperature is 350°C to 450°C; and / or

[0029] The heat treatment time is 1h to 5h; and / or

[0030] The atmosphere of the heat treatment process is an inert gas atmosphere such as nitrogen atmosphere or argon atmosphere.

[0031] As an optional embodiment, the heating rate of the carbonization treatment is 1°C / min to 10°C / min; and / or

[0032] The temperature of the carbonization treatment is 700°C to 1000°C; and / or

[0033] The carbonization treatment time is 1h to 4h; and / or

[0034] The atmosphere of the carbonization process is an inert gas atmosphere such as nitrogen atmosphere or argon atmosphere.

[0035] As an optional embodiment, the diameter of the core is 20nm to 50nm; and / or

[0036] The thickness of the shell layer is 5nm to 15nm.

[0037] In the above embodiment, the appropriate core diameter is conducive to the size of the carbon carrier accumulation pores. The core diameter is controlled to be 20nm to 50nm, which can make the accumulation pores of the carbon carrier within a suitable range. The shell thickness is positively correlated with the pore depth to a certain extent. The shell thickness is controlled to be 5nm to 15nm, so that the pore depth is within a suitable range, and then the depth of the loading position of the catalytically active substance is within a suitable range, thereby improving the utilization rate of the catalytically active substance.

[0038] In a second aspect, an embodiment of the present application provides a carbon carrier, which is prepared by the method provided in the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 A flowchart of the method provided in the embodiment of the present application. DETAILED DESCRIPTION

[0041] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0042] Figure 1 A flow chart of the method provided in the embodiment of the present application is as follows: Figure 1 As shown, the present application embodiment provides a method for preparing a carbon carrier, the method comprising:

[0043] S1. obtaining a precursor, wherein the precursor comprises a core and a shell, wherein the core comprises a first carbon source, and the shell comprises a second carbon source and a template pore-forming agent, wherein the first carbon source and the second carbon source are the same;

[0044] In some embodiments, the first carbon source and the second carbon source include phenolic resin. In some embodiments, the template pore forming agent can be selected from at least one of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer (F127), polyethylene oxide-polyoxypropylene-polyoxyethylene triblock copolymer (P123), etc. The weight average molecular weight of the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer is about 12600, and the weight average molecular weight of the polyethylene oxide-polyoxypropylene-polyoxyethylene triblock copolymer is about 5800.

[0045] In some embodiments, the precursor is obtained by: S1.1. Mixing the core raw material with a solvent to obtain a first mixture; S1.2. Polymerizing the first mixture to obtain a solution containing the core; S1.3. Mixing the solution containing the core, the shell raw material and the template pore-forming agent to obtain a second mixture; S1.4. Polymerizing the second mixture to obtain a precursor; wherein the core raw material and the shell raw material are the same, and the core raw material includes phenol and its derivatives and aldehydes. The one-pot method is used to first obtain the core, and then continue to add the shell raw material, and continue to grow on the basis of the core to obtain the precursor, which can reduce the probability of core adhesion, and can achieve a single core corresponding to a single shell as much as possible, so as to achieve better coating of the core.

[0046] Among them, in the first mixture, the molar concentration of the phenol and its derivatives is 0.01mol / mL to 0.1mol / mL; the molar concentration of the aldehyde substance is 0.01mol / mL to 0.1mol / mL; the first mixture also includes an alkaline catalyst, and the alkaline catalyst includes at least one of ammonia water, potassium hydroxide and sodium hydroxide; the pH value of the first mixture is 9 to 13. By controlling the concentration of phenol and its derivatives, the concentration of aldehyde substances, and the pH value of the reaction system during the polymerization process of the core, it is beneficial to form a better phenolic resin as a core carbon source, and then it is beneficial to form a high-quality carbon carrier core.

[0047] Exemplarily, in the first mixed material, the molar concentration of phenol and its derivatives can be 0.01mol / mL, 0.02mol / mL, 0.03mol / mL, 0.04mol / mL, 0.05mol / mL, 0.06mol / mL, 0.07mol / mL, 0.08mol / mL, 0.09mol / mL, 0.1mol / mL, etc., which can also be any value in the range of 0.01mol / mL to 0.1mol / mL. The molar concentration of aldehydes can be 0.01mol / mL, 0.02mol / mL, 0.03mol / mL, 0.04mol / mL, 0.05mol / mL, 0.06mol / mL, 0.07mol / mL, 0.08mol / mL, 0.09mol / mL, 0.1mol / mL, etc., which can also be any value in the range of 0.01mol / mL to 0.1mol / mL. The pH value of the first mixture can be 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, etc. It can also be any value within the range of 9 to 13.

[0048] Among them, in the second mixture, the molar concentration of the phenol and its derivatives is 0.01mol / mL to 0.1mol / mL; the molar concentration of the aldehyde substance is 0.01mol / mL to 0.1mol / mL; the molar concentration of the template pore-forming agent is 0.01mol / mL to 0.1mol / mL. By controlling the concentration of phenol and its derivatives, the concentration of the aldehyde substance, and the concentration of the template pore-forming agent during the polymerization process of the shell layer, it is beneficial to form a better phenolic resin as a shell carbon source and better pores, which is beneficial to the formation of a high-quality carbon carrier shell layer.

[0049] Exemplarily, in the second mixed material, the molar concentration of phenol and its derivatives can be 0.01mol / mL, 0.02mol / mL, 0.03mol / mL, 0.04mol / mL, 0.05mol / mL, 0.06mol / mL, 0.07mol / mL, 0.08mol / mL, 0.09mol / mL, 0.1mol / mL, etc., which can also be any value in the range of 0.01mol / mL to 0.1mol / mL. The molar concentration of aldehydes can be 0.01mol / mL, 0.02mol / mL, 0.03mol / mL, 0.04mol / mL, 0.05mol / mL, 0.06mol / mL, 0.07mol / mL, 0.08mol / mL, 0.09mol / mL, 0.1mol / mL, etc., which can also be any value in the range of 0.01mol / mL to 0.1mol / mL. The molar concentration of the template pore former can be 0.01 mol / mL, 0.02 mol / mL, 0.03 mol / mL, 0.04 mol / mL, 0.05 mol / mL, 0.06 mol / mL, 0.07 mol / mL, 0.08 mol / mL, 0.09 mol / mL, 0.1 mol / mL, etc., and it can also be any value within the range of 0.01 mol / mL to 0.1 mol / mL.

[0050] Specifically, in this embodiment, phenol and formaldehyde are dissolved in water, the pH is adjusted to alkaline, and the polymerization is stirred at 40°C to 80°C for 2 to 10 hours to obtain a core-containing solution; wherein the concentration of phenol is 0.01 mol / mL to 0.1 mol / mL, the ratio of formaldehyde to phenol is 1:1, and the alkali used can be ammonia water, potassium hydroxide, or sodium hydroxide, and the pH range is 9 to 13. Phenol and formaldehyde are added to the polymerization-completed solution, and a template is added, and stirred evenly; the polymerization is stirred at 40°C to 80°C for 2 to 10 hours; after the reaction is completed, the product is filtered and washed, and dried at 60°C to 80°C to obtain a precursor.

[0051] Exemplarily, in this embodiment, the temperature of the polymerization reaction can be 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., etc., and it can also be any value in the range of 40° C. to 80° C. The time of the polymerization reaction can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, etc., and it can also be any value in the range of 2 to 10 hours.

[0052] S2. heat-treating the precursor to remove the template pore-forming agent in the shell layer of the precursor, and carbonizing the precursor to obtain a carbon carrier.

[0053] In some embodiments, the heating rate of the heat treatment is 0.5°C / min to 3°C / min; the temperature of the heat treatment is 350°C to 450°C; the time of the heat treatment is 1h to 5h; the atmosphere of the heat treatment process is an inert gas atmosphere such as nitrogen atmosphere or argon.

[0054] Specifically, in this embodiment, the heat treatment process can be: heating the precursor to 300°C to 450°C at a rate of 0.5°C / min to 3°C / min, and keeping it warm for 1h to 5h to remove the template pore-forming agent in the shell layer of the precursor, wherein the atmosphere of the removal process is a nitrogen atmosphere and / or an inert gas atmosphere.

[0055] Exemplarily, in this embodiment, the heating rate of the removal process can be 0.5°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, etc., and it can also be any value in the range of 0.5°C / min to 3°C / min. The terminal temperature of the removal process can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, etc., and it can also be any value in the range of 300°C to 450°C. The insulation time of the removal process can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, etc., and it can also be any value in the range of 1h to 5h.

[0056] In some embodiments, the heating rate of the carbonization treatment is 1°C / min to 10°C / min; the temperature of the carbonization treatment is 700°C to 1000°C; the time of the carbonization treatment is 1h to 4h; the atmosphere of the carbonization treatment process is an inert gas atmosphere such as nitrogen atmosphere or argon.

[0057] Specifically, in this embodiment, the carbonization treatment process can be: heating to 700°C to 1000°C at a rate of 1°C / min to 10°C / min, and keeping warm for 1h to 4h to perform carbonization treatment to obtain a carbon carrier, wherein the atmosphere of the carbonization treatment process is an inert gas atmosphere such as nitrogen atmosphere or argon.

[0058] Exemplarily, in this embodiment, the heating rate of the carbonization process is 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc., which can also be any value in the range of 1°C / min to 10°C / min. The terminal temperature of the carbonization process can be 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, 920°C, 940°C, 960°C, 980°C, 1000°C, etc., which can also be any value in the range of 700°C to 1000°C. The holding time of the carbonization process can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, etc., and can also be any value within the range of 1h to 4h.

[0059] This method uses the same carbon source as the core and shell components of the precursor. In the subsequent heat treatment process, such as carbonization treatment, the decomposition degree and shrinkage degree of the core and shell are consistent, which can reduce the phenomenon of core-shell separation of the core-shell structured carbon material. At the same time, the use of a template pore-forming agent to form pores in the shell will not produce an etching effect on the core like the pore-forming methods such as carbon dioxide activation, thereby avoiding the formation of holes in the core. In addition, the core size and shell thickness of the carbon carrier prepared by this method are controllable, which is conducive to adjusting the stacking pore size and pore-forming depth.

[0060] Based on a general inventive concept, an embodiment of the present application further provides a carbon carrier, which is prepared by the method provided above.

[0061] The carbon carrier is realized based on the above method. The specific steps of the method can refer to the above embodiment. Since the carbon carrier adopts part or all of the technical solutions of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, which will not be described one by one here.

[0062] The carbon carrier has a core-shell structure, with a solid carbon sphere as the core and a mesoporous carbon layer as the shell. The core and the shell are made of the same material, and the graphitization degree inside and outside is consistent after heat treatment; no other metal impurities are introduced during the synthesis process; the thickness of the outer mesoporous carbon layer can be controlled to be 5-15nm, which is conducive to the loading of catalytically active substances in shallow pores and improving the utilization rate of catalytically active substances. The core size can be adjusted, that is, the size of the final product can be adjusted, and the appropriate carbon carrier size can be used to adjust the stacking pore size of the carbon carrier.

[0063] In some embodiments, the diameter of the carbon carrier core is 20nm to 50nm; the thickness of the carbon carrier shell is 5nm to 15nm. The appropriate core diameter is conducive to the size of the carbon carrier stacking pores. Controlling the core diameter to 20nm to 50nm can make the stacking pores of the carbon carrier within a suitable range. The shell thickness is positively correlated with the pore depth to a certain extent. Controlling the shell thickness to 5nm to 15nm can make the pore depth within a suitable range, thereby making the depth of the loading position of the catalytically active substance within a suitable range and improving the utilization rate of the catalytically active substance.

[0064] The carbon carrier can form a catalyst by loading some catalytically active substances, such as platinum and its alloys.

[0065] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0066] Example 1

[0067] A carbon carrier, the preparation method of which comprises the following steps:

[0068] (1) Phenol and formaldehyde are dissolved in water, the pH is adjusted to be alkaline, and polymerization is carried out by stirring at 40° C. for 2 hours; wherein the concentration of phenol is 0.01 mol / mL, the ratio of formaldehyde to phenol is in the range of 1:1, the base used is ammonia water, and the pH range is 9.

[0069] (2) Add phenol and formaldehyde to the polymerization solution, and add a template agent, and stir evenly; wherein the concentration of phenol is 0.01 mol / mL, the ratio of formaldehyde to phenol is 1:1, and the template agent is F127, and the concentration is 0.01 g / mL.

[0070] (3) stirring polymerization at 40°C for 2 hours;

[0071] (4) After the reaction is completed, the product is filtered and washed, and dried at 60° C. to obtain a precursor;

[0072] (5) Removing the template pore-forming agent in the shell layer of the precursor to obtain an intermediate precursor, wherein the inert gas is nitrogen. The temperature is raised to 300°C at a rate of 0.5°C / min and kept at this temperature for 1 hour.

[0073] (6) The intermediate precursor is carbonized to obtain a core-shell carbon carrier, wherein the inert gas is nitrogen. The temperature is raised to 700°C at a rate of 1°C / min and kept at this temperature for 1 hour.

[0074] Example 2

[0075] A carbon carrier, the preparation method of which comprises the following steps:

[0076] (1) Phenol and formaldehyde are dissolved in water, the pH is adjusted to be alkaline, and polymerization is carried out by stirring at 60° C. for 6 hours; wherein the concentration of phenol is 0.05 mol / mL, the ratio of formaldehyde to phenol is in the range of 1:1, the base used is ammonia water, and the pH range is 11.

[0077] (2) Add phenol and formaldehyde to the polymerization solution, and add a template agent, and stir evenly; wherein the concentration of phenol is 0.05 mol / mL, the ratio of formaldehyde to phenol is 1:1, and the template agent is F127 with a concentration of 0.05 g / mL.

[0078] (3) stirring polymerization at 60°C for 6 hours;

[0079] (4) After the reaction is completed, the product is filtered and washed, and dried at 70° C. to obtain a precursor;

[0080] (5) Removing the template pore-forming agent in the shell layer of the precursor to obtain an intermediate precursor, wherein the inert gas is nitrogen. The temperature is raised to 375°C at a rate of 2°C / min and kept at this temperature for 3 hours.

[0081] (6) The intermediate precursor is carbonized to obtain a core-shell carbon carrier, wherein the inert gas is argon. The temperature is raised to 850°C at a rate of 5°C / min and kept at this temperature for 2.5 hours.

[0082] Example 3

[0083] A carbon carrier, the preparation method of which comprises the following steps:

[0084] (1) Phenol and formaldehyde are dissolved in water, the pH is adjusted to be alkaline, and polymerization is carried out at 80° C. with stirring for 10 hours; wherein the concentration of phenol is 0.1 mol / mL, the ratio of formaldehyde to phenol is in the range of 1:1, the base used is ammonia water, and the pH range is 13.

[0085] (2) Add phenol and formaldehyde to the polymerization solution, and add a template agent, and stir evenly; wherein the concentration of phenol is 0.1 mol / mL, the ratio of formaldehyde to phenol is 1:1, and the template agent is F127, and the concentration is 0.1 g / mL.

[0086] (3) stirring polymerization at 80°C for 10 hours;

[0087] (4) After the reaction is completed, the product is filtered and washed, and dried at 80° C. to obtain a precursor;

[0088] (5) Removing the template pore-forming agent in the shell layer of the precursor to obtain an intermediate precursor, wherein the inert gas is argon. The temperature is raised to 450°C at a rate of 3°C / min and kept at this temperature for 5 hours.

[0089] (6) Carbonizing the intermediate precursor to obtain a core-shell carbon carrier, wherein the inert gas is argon. The temperature is raised to 1000°C at a rate of 10°C / min and kept at this temperature for 1-4 hours.

[0090] Comparative Example 1

[0091] A carbon carrier (fully mesoporous carbon), the preparation method of which comprises the following steps:

[0092] (1) Phenol and formaldehyde were dissolved in water, and a template agent was added, the pH was adjusted to be alkaline, and the polymerization was carried out by stirring at 40°C for 2 hours; wherein the concentration of phenol was 0.05 mol / mL, the ratio of formaldehyde to phenol was 1:1, the base used was ammonia water, and the pH range was 9. The template agent was F127, and the concentration was 0.05 g / mL;

[0093] (2) stirring polymerization at 60°C for 6 hours;

[0094] (3) After the reaction is completed, the product is filtered and washed, and dried at 70° C. to obtain a precursor;

[0095] (4) Heat treatment to remove the template pore-forming agent of the precursor, wherein the inert gas is nitrogen. The temperature is raised to 375°C at a rate of 2°C / min and kept at that temperature for 1 hour. The temperature is then raised to 700°C at a rate of 1°C / min and kept at that temperature for 1 hour.

[0096] Comparative Example 2

[0097] A carbon carrier (non-mesoporous carbon), the preparation method of which comprises the following steps:

[0098] (1) Phenol and formaldehyde are dissolved in water, the pH is adjusted to be alkaline, and polymerization is carried out by stirring at 40° C. for 2 hours; wherein the concentration of phenol is 0.05 mol / mL, the ratio of formaldehyde to phenol is in the range of 1:1, the base used is ammonia water, and the pH range is 9.

[0099] (2) stirring polymerization at 60°C for 6 hours;

[0100] (3) After the reaction is completed, the product is filtered and washed, and dried at 70° C. to obtain a precursor;

[0101] (4) Heat treatment to obtain non-mesoporous carbon, wherein the inert gas is nitrogen. The temperature is raised to 700°C at a rate of 1°C / min and kept at this temperature for 1 hour.

[0102] The carbon carriers provided in each embodiment and comparative example were subjected to morphological testing, and the testing included:

[0103] Detection of core diameter and shell thickness: measured by TEM test. The core diameter is the size of solid carbon obtained by direct heat treatment without shell coverage. The shell thickness is half of the diameter of the core-shell carbon carrier minus the diameter of the solid carbon. Comparative Example 1 is mesoporous carbon, and the thickness of the mesoporous layer is the radius of the sphere. Comparative Example 2 is solid carbon, and the core diameter is the diameter of the sphere.

[0104] Specific surface area and mesopore diameter detection: obtained through BET and BJH tests.

[0105] The results are shown in the following table:

[0106]

[0107]

[0108] It can be seen from the above table that the carbon carrier prepared by the method provided in the embodiment of the present application can control the core size and shell thickness by adjusting the raw material concentration, polymerization time and temperature.

[0109] The carbon carriers provided in each embodiment and comparative example are loaded with catalytically active substances to form catalysts, and the loading process is as follows: the carbon carrier and chloroplatinic acid are fully dissolved, mixed and dispersed, and the metal ions are reduced to nano-metal particles by the action of a reducing agent in the liquid phase; or, the intermediate product is heat-treated under a reducing atmosphere to reduce the metal ions to nano-metal particles.

[0110] The specific liquid phase reduction or gas phase reduction method can refer to the relevant technology.

[0111] In the liquid phase, the metal ions are reduced to nano-metal particles by the action of a reducing agent, that is, a liquid phase reduction method is adopted, wherein the reducing agent in the liquid phase reduction method includes but is not limited to polyols, sodium borohydride, formaldehyde, formic acid, etc., which can be selected according to actual needs. For example, the reduction is carried out by heating to 120°C-160°C in a polyol, wherein the liquid phase reduction can be assisted by microwave heating for reduction, which is conducive to reducing the metal ions to nano-metal particles.

[0112] Heat treatment of the intermediate product under a reducing atmosphere is also known as gas phase reduction, wherein the gas phase reduction atmosphere includes but is not limited to heat treatment at 200°C-700°C for 0.5h-4h in a reducing atmosphere of hydrogen and / or carbon monoxide, or in a reducing atmosphere of a mixture of hydrogen and an inert gas.

[0113] And the performance of the loaded catalyst was tested:

[0114] Electrochemical active area and mass activity test: Through a series of electrochemical tests (cyclic voltammetry CV, linear sweep voltammetry LSV, etc.), the oxygen reduction activity and durability of the catalyst are studied. Generally, the electrochemical active area ECSA and mass activity MA are used to judge the ORR performance.

[0115] CV test: Place the electrodes in an electrolytic cell to form a three-electrode system. The reference electrode is Hg / Hg2SO4, the counter electrode is a platinum mesh electrode, and the electrolyte is a 0.5M H2SO4 solution saturated with N2 and kept at a constant temperature of 25°C. Open the software, set the scan rate in the CV test window to 50m / s, and scan 20 times (10 cycles) at -0.632 to 0.328V to fully activate the catalyst and stabilize the complex desorption peak. Calculate the electrochemical active area ECSA of the catalyst based on the data of the last cycle.

[0116] Linear sweep voltammetry: In order to evaluate the ORR electrocatalytic performance of the catalyst materials and their performance in the reaction process, cathode polarization measurements were performed and the linear sweep voltammetry (LSV) results were used for judgment. LSV test: The LSV test window was replaced with an O2-saturated 0.1M HC1O4 electrolytic cell (for IR compensation), and the working electrode was kept at a speed of 1600rpm. Scanning was performed at -0.26 to 0.695V at a scan rate of 10mV / s. The kinetic current density was calculated from the measured current density and the limiting current density, and the MA was calculated from the kinetic current density and the actual mass of the precious metal.

[0117] The results are shown in the following table:

[0118]

[0119] It can be seen from the above table that the carbon carrier prepared by the method provided in the examples of the present application can improve the mass activity of the catalytically active substance when it is used as a catalyst after being loaded with a catalytically active substance.

[0120] The above description is only a specific embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a carbon carrier, characterized in that: The method comprises: Obtaining a precursor, the precursor comprising a core and a shell, the core comprising a first carbon source, the shell comprising a second carbon source and a template pore-forming agent, the first carbon source and the second carbon source being the same; The precursor is heat-treated to remove the template pore-forming agent in the shell layer of the precursor, and carbonized to obtain a carbon carrier.

2. The method for preparing a carbon carrier according to claim 1, characterized in that: The first carbon source and the second carbon source include phenolic resin.

3. The method for preparing a carbon carrier according to claim 1, characterized in that: The template pore former includes a polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer and / or a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer.

4. The method for preparing a carbon carrier according to claim 1, characterized in that: The obtained precursor comprises: Mixing the core raw material with a solvent to obtain a first mixed material; subjecting the first mixed material to a polymerization reaction to obtain a solution containing a core; Mixing the core-containing solution, shell layer raw materials and template pore-forming agent to obtain a second mixed material; subjecting the second mixed material to polymerization reaction to obtain a precursor; The core raw material is the same as the shell raw material, and the core raw material includes phenol and its derivatives and aldehyde substances.

5. The method for preparing a carbon carrier according to claim 4, characterized in that: In the first mixed material, the molar concentration of the phenol and its derivatives is 0.01 mol / mL to 0.1 mol / mL; In the first mixed material, the molar concentration of the aldehyde substance is 0.01 mol / mL to 0.1 mol / mL; The first mixture also includes an alkaline catalyst, and the alkaline catalyst includes at least one of ammonia water, potassium hydroxide and sodium hydroxide; The pH value of the first mixed material is 9-13.

6. The method for preparing a carbon carrier according to claim 4, characterized in that: In the second mixed material, the molar concentration of the phenol and its derivatives is 0.01 mol / mL to 0.1 mol / mL; and / or In the second mixed material, the molar concentration of the aldehyde substance is 0.01 mol / mL to 0.1 mol / mL; In the second mixed material, the molar concentration of the template pore-forming agent is 0.01 mol / mL to 0.1 mol / mL.

7. The method for preparing a carbon carrier according to claim 1, characterized in that: The heating rate of the heat treatment is 0.5°C / min to 3°C / min; and / or The heat treatment temperature is 350°C to 450°C; and / or The heat treatment time is 1h to 5h; and / or The atmosphere of the heat treatment process is a nitrogen atmosphere or an inert gas atmosphere.

8. The method for preparing a carbon carrier according to claim 1, characterized in that: The heating rate of the carbonization treatment is 1°C / min to 10°C / min; and / or The temperature of the carbonization treatment is 700°C to 1000°C; and / or The carbonization treatment time is 1h to 4h; and / or The atmosphere during the carbonization treatment process is a nitrogen atmosphere or an inert gas atmosphere.

9. The method for preparing a carbon carrier according to claim 1, characterized in that: The diameter of the core is 20nm-50nm; the thickness of the shell is 5nm-15nm.

10. A carbon carrier, characterized in that The carbon carrier is prepared by the method according to any one of claims 1 to 9.